2021
DOI: 10.3389/fmicb.2020.609952
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Metabolites From Acid-Tolerant Fungi in a Thai Mangrove Sediment

Abstract: Despite being potentially useful extremophile resources, there have been few reports on acid-tolerant fungi and their bioactive metabolites. Acidophilic/aciduric fungi (n = 237) were isolated from Thai mangrove sediments in an acidic medium. Using fungal identification technology (including morphologic observation, chemical screening, and sequence comparisons) all the isolates were identified and 41 representative isolates were selected for analysis of the phylogenetic relationships (ITS rDNA, β-tubulin, calmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Those microorganisms also have the potential to produce bioactive metabolites, which can be harnessed for industrial and medicinal purposes. Fungi isolated from mangrove soils were reported to produce industrial enzymes such as lipase, cellulase, protease, and pectinase and therapeutic compounds such as antimicrobials, antivirals, antioxidants, and anticancer (Gao et al 2021;Sopalun et al 2021). Meanwhile, bacterial strains isolated from mangrove soils produced antimicrobials, anti-inflammatory, and antioxidant compounds (Qureshi et al 2020;Rajan et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Those microorganisms also have the potential to produce bioactive metabolites, which can be harnessed for industrial and medicinal purposes. Fungi isolated from mangrove soils were reported to produce industrial enzymes such as lipase, cellulase, protease, and pectinase and therapeutic compounds such as antimicrobials, antivirals, antioxidants, and anticancer (Gao et al 2021;Sopalun et al 2021). Meanwhile, bacterial strains isolated from mangrove soils produced antimicrobials, anti-inflammatory, and antioxidant compounds (Qureshi et al 2020;Rajan et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…2017), an ultra-acidic soil environment might potentially offer new biotechnologically interesting fungi, especially in terms of enzyme production. Also, thermophilic fungi, particularly the species Talaromaces but also Aspergillus, Cladosporium and Trichoderma, can represent a rich source of industrially relevant enzymes at pH 2.0 (Gao et al, 2021;Thang et al, 2019). The effect of soil acidi cation showed that pH is an essential predictor for controlling the distribution of microbial communities, and fungal communities exhibit little response to soil acidity (Wang et al, 2022).…”
Section: Plant Community Structurementioning
confidence: 99%
“…Such studies are also of interest for astrobiology, since fungi are the key organisms in the search for the limits of life on Earth and in the Universe and ecology—for the preservation of biocenoses despite abrupt climate changes and increased anthropogenic influence. Extremophiles are used for bioremediation and biofuel production and are also sources of new biologically active compounds and extremozymes [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%